Metabolic Syndrome in patients with Urinary Tract Stone Disease: A Hospital based Single Center Study - Ali, Rushdulla; Sigdel, Mahesh R (Journal of Institute of Medicine Nepal, 2023)
Introduction Patients with urinary tract stones (UTS) are at an increased risk of developing metabolic syndrome (MetS). Assessment for MetS could be useful for patients presenting with UTS. We assessed the prevalence of MetS and each of its components in patients with UTS. Correlation of 24-hour urinary and serum calcium and uric acid levels with components of MetS was also done. Methods A cross-sectional study was conducted at Tribuvan University Teaching Hospital, Institute of Medicine (IOM) from August 2021 and July 2022. After the approval from the Institutional Review Committee, 118 consenting adult patients with unilateral or bilateral UTS who fulfilled inclusion criteria were studied. Patients with congenital renal abnormalities, ADPKD, advanced chronic kidney disease with eGFR of <30 ml/min/1.73m2, proven metabolic causes of stone disease, those with cancer and pregnant women were not included. All patients underwent measurement of waist circumference, systolic and diastolic blood pressure, fasting blood sugar, serum triglycerides, high density lipoprotein cholesterol, uric acid, calcium, electrocardiography (ECG), renal function test, and 24-hour urinary calcium and uric acid. MetS was defined as per The International Diabetic Federation criteria. SPSS Version 25.0 was used for statistical analysis. Results Thirty-five (29.7%) stone formers had MetS. Among them, 23 (65.7%) were males, and 12 (34.3%) females. The mean body mass index (BMI) of patients with MetS was 25.96 ± 4.62 kg/m2. In patients with MetS, 24 (68.8%) had high BP and impaired plasma FBS. Twenty-one (60.0%) patients had increased serum triglyceride levels, and 54.3% had reduced HDL-cholesterol. Systolic Blood Pressure (SBP) had a significant correlation with hypercalciuria (P=0.011) and hyperuricemia (P=0.046). Serum triglyceride (TG) levels was significantly correlated with hypercalcemia (P=0.045). The mean estimated glomerular filtration rate (eGFR) of the study population was 83.48 ± 32.37 mL/min/1.73 m2. Conclusion Patients with urinary tract stone disease are associated with metabolic syndrome. Assessment for metabolic syndrome should be considered in patients with urinary tract stone disease.